Qualidade do relato integrado: uma análise à luz da teoria dos stakeholders - Laiz de Fátima Carvalho (2021)
The objective of this research was to analyze how the pressure from the Government, Employees and Shareholders affects the quality of the Integrated Report published by the companies listed on the Brazil 100 Index (IBr X100 B3) in the period from 2013 to 2019. This study was classified as quantitative in relation to the approach to the problem, as descriptive in terms of objectives, as bibliographic and documentary in relation to procedures and as ex post facto. The sample consisted of 37 companies. The theoretical platform addressed issues related to the importance of information quality in the corporate environment, the Integrated Report and its structure, in addition to presenting the main theory that underlies this research, the Stakeholder Theory. For the operationalization of the study, an index was built to measure the quality of the Integrated Reports released by the companies. In order to complement the analysis of the quality index, the factor analysis technique was applied to point out the most relevant variables for the construction of the general index. Additionally, the GLS panel data model was used to analyze whether Stakeholder pressure affects the quality of the IR. Empirical evidence pointed out that only employees exert pressure when analyzing the overall Integrated Reporting Quality index. Government pressure was only observed when the Factor (2), composed of information related to the business model and performance, was analyzed in isolation. However, this impact becomes negative when the quality proxy of the Report is given by the Factor (3), composed of information related to the strategy, the allocation of resources and the basis and preparation. Regarding the pressure from shareholders, it was not possible to capture any influence based on the sample explored in this research, not even when the factors were analyzed individually. This may be associated with data limitation. It was also possible to infer that, in general, the level of corporate governance and the sectors of economic activity affect the quality of Integrated Reporting. Research on this topic can encourage discussions within organizations that aim to improve the quality of information disclosed to interested parties. Since, Integrated Reporting is a new approach, especially in the Brazilian context, little is known about this new way of reporting. Therefore, this study can provide subsidies for companies to understand the gain that IR can bring mainly with relations with Stakeholders. Especially because, the financial reports for the most part have limitations, as there are many elements that are important for showing the companies' value creation, but are not captured in these reports. Thus, shareholders and other interested parties need to understand the company as a whole, from the business model to its social actions and environments, then demonstrate how RI can help expand the vision and help companies in the preparation of these reports. And when organizations improve the quality of information, decision-making will possibly be more assertive.